Privatisation method effects on performance and market orientation of Central/Eastern European companies - Tony Cox; Graham J. Hooley; John Fahy; József Beracs; Krzysztof Fonfara; Boris Snoj (Journal for East European Management Studies, 1998)
Privatisation in Central and Eastern Europe was introduced to encourage competition in companies with subsequent beneficial effects on company performance and market orientation. Companies have been privatised by four main methods in these countries depending on the company circumstances before privatisation and leading to different dominant stakeholders after the privatisation. The performance and market orientation of companies privatised by each method are surveyed by mailed questionnaires and differences are found that are attributable to different stakeholder influence as a result of the privatisation method. – – Privatisierungen wurden in Mittel- und Osteuropa durchgeführt, um den Wettbewerb anzukurbeln, welcher in der Nachfolge positive Effekte auf Unternehmensleistung und Marktorientierung haben sollte. Unternehmen in diesen Ländern wurden nach vier verschiedenen Methoden privatisiert, abhängig davon, in welchen Umständen sich das jeweilige Unternehmen vor der Privatisierung befand. Je nach Methode führte die Privatisierung zu verschiedenartigen Hauptanteilseignern. Die Leistung und Marktorientierung von Unternehmen, die je nach einer der vier Methoden privatisiert wurden, wurde anhand von Fragebögen untersucht und es haben sich Unterschiede gezeigt, die aufgrund der verschiedenen Möglichkeiten zur Einflußnahme seitens der Anteilseigner zustande kommen.
Keywords: 650